Management of Track Records Data an Impact on Buying Decision by Customers Online Stores - Faisal Umardani Hasibuan; Ruqaiyah Ruqaiyah (Journal of Management and Business Innovations, 2021)
This study aimed to analyze the effect of online customer review/rating and online vlogger review on purchasing decisions in online shop applications. This type of research is quantitative research. The data used in this study are primary data obtained from questionnaires using google from which were distributed to students of the Islamic economics and business faculty of (FEBI) IAIN Langsa who have shopped at the online shop application and know how to use the online shop application. The sampling technique used in this research is the purposive sampling method, the number of samples that the authors use is 94 samples. This study concluded that the online customer review rating tested jointly did not have a positive effect but significantly influenced purchasing decisions on the online shop application with several 2,419 < 2,630, vlogger reviews had a positive and significant influence on buyer decisions with the number 3,620 > 2,630. Simultaneously, online customer reviews and vlogger reviews positively influence purchasing decisions on online shop applications with numbers 36,314 > 4.84.Keywords: Buying decision, online customer review/rating, online vloger review